The Abuse Of Anabolic Steroids - Abd Razak, Dzulkifli (1996)
ANABOLIC STEROIDS, ONE OF THE classes of banned doping agents listed by the International Olympic Committee (IOC), are derivatives of, and include the male hormone, testosterone. This hormone is a normal body chemical, present in every normal person but a different levels. It is produced naturally by the body to promote, regulate and maintain physical and sexual development in males. It is released from the testes and arenal glands in males and the adrenal glands in females, and is of course in low concentrations in the blood of women. Biologically, testosterone is regulated by what is called "the negative feedback" principle. This is a well established and long known biological control system where the"end product" chemical feeds back into its own regulating system to switch off its own production at generically determined levels for each individual.